2023
DOI: 10.1186/s40645-023-00579-7
|View full text |Cite
|
Sign up to set email alerts
|

Incoming plate structure at the Japan Trench subduction zone revealed in densely spaced reflection seismic profiles

Abstract: The structure of the incoming plate is an important element that is often considered to be related to the occurrence of great earthquakes in subduction zones. In the Japan Trench, where the 2011 Tohoku earthquake occurred, we collected seismic profiles along survey lines separated by 2–8 km to examine the structural characteristics of the incoming Pacific plate in detail. The average thickness of the incoming sediments was < 500 m along most of the Japan Trench, and it was < 300 m at ~ 38° N, where the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…We map seismic units on the incoming and overriding plate in the study area using the seismic stratigraphy of Nakamura et al (2013Nakamura et al ( , 2020Nakamura et al ( , 2023 (Figure 2a). This work defines four seismic units (SU1 though SU4) based on seismic characteristics and correlations to known seismic and lithostratigraphic units of DSDP Site 436 and International Ocean Drilling Program (IODP) Expedition 343 Core C0019 (Nakamura et al, 2013).…”
Section: Seismic Line Mappingmentioning
confidence: 99%
See 3 more Smart Citations
“…We map seismic units on the incoming and overriding plate in the study area using the seismic stratigraphy of Nakamura et al (2013Nakamura et al ( , 2020Nakamura et al ( , 2023 (Figure 2a). This work defines four seismic units (SU1 though SU4) based on seismic characteristics and correlations to known seismic and lithostratigraphic units of DSDP Site 436 and International Ocean Drilling Program (IODP) Expedition 343 Core C0019 (Nakamura et al, 2013).…”
Section: Seismic Line Mappingmentioning
confidence: 99%
“…This unit is correlative to incoming plate sediments composed of diatomaceous muds with a basal pelagic clay layer (Nakamura et al, 2013). We include trench fill deposits, parallel and continuous reflections that overly the incoming plate sediments near the deformation front, as part of the SU2 map unit (Nakamura et al, 2023). Seismic unit SU3 contains high amplitude, sub-horizontal, semi-continuous reflections and is correlated to a chert layer stratigraphically below SU2.…”
Section: Seismic Line Mappingmentioning
confidence: 99%
See 2 more Smart Citations
“…For the other four events (20110322, 20110603, 20110817, and 20170920), we find that all of them tend to take place on the trench-ward dipping faults (Figure 9). It is interesting that Nakamura et al (2023) used seismic profiles to infer the dipping directions of the outer-rise normal faults in the region and also found that similar results of more trench-ward dipping faults than that dip ocean-ward. Note that the centroid depths of these events gradually increase with distance from the trench, which could be explained by a deeper neutral stress axis (the transition from extension to compression) related to the bending and elastic thickness of the subducting plate.…”
Section: Ruptured Fault Plane Determinationmentioning
confidence: 99%